2020
DOI: 10.18535/ijsrm/v8i03.el02
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between Parental Level of Education and Learners Performance in Public Pre -Primary schools in Nandi County, Kenya.

Abstract: Factors related with parental involvement on their childrens education continues to be a pertinent issue. Some school going children in Kenya post detrimental results amid claims that parents are not supportive. This study sought to establish influence of Parental Level of Education on Pre-PrimaryLearners performance in curriculum activities in Nandi County, Kenya. Epsteins Theory and descriptive survey design was used for the study. Purposive sampling technique, stratified random technique and simple random t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
0
4
0
1
Order By: Relevance
“…Similar studies on educational level of parents and students' performance in foreign language learning indicated that the level of education of parents significantly influence students' learning (Bakar, Mamat & Ibrahim, 2017;Chemagosi, 2020;Musarat et. al, 2013;Odoh, Ugwuanyi, Odigbo & Chukwuani, 2017).…”
Section: Literature Reviewmentioning
confidence: 77%
“…Similar studies on educational level of parents and students' performance in foreign language learning indicated that the level of education of parents significantly influence students' learning (Bakar, Mamat & Ibrahim, 2017;Chemagosi, 2020;Musarat et. al, 2013;Odoh, Ugwuanyi, Odigbo & Chukwuani, 2017).…”
Section: Literature Reviewmentioning
confidence: 77%
“…Children with uninvolved parents are likely to have low levels of functioning in many areas. They tend to do poorly in schools and particularly as they move into high school, are more likely to exhibit delinquent behaviour and to be depressed (Chemagosi, 2016). Parents who do not know what their children are doing at schools and leave everything to teachers and siblings may results into children not getting what they (parents) wish their children to get from the learning environment.…”
Section: Resultsmentioning
confidence: 99%
“…The above findings confirm the findings made in Nadenge's (2015) study, which reported the existence of a significant positive relationship between parental involvement, good parentteacher relationships and academic performance. Similarly, Chemagosi, Odongo and Aloka (2016) found collaborative effort among school, family and community to enhance children's learning always results in the improved academic performance of children, reducing the chances of dropout and children enjoying schooling. Likewise, Kibaara and Ndirangu (2014) found a remarkable boost in learners' academic performance, when there is positive parental involvement in their academic journey.…”
Section: The Effect Of Parental Involvement On the Academic Achieveme...mentioning
confidence: 97%
“…These definitions demonstrate the multifaceted nature of parent involvement and indicate that the concept subsumes a wide variety of home-school activities and parenting practices (Harris & Goodall, 2008;Roy & Giraldo-García, 2018). However, while definitions of parent involvement may vary, researchers unanimously agree that when schools, families and community members collaborate to provide support for their children's education, the children involved tend to perform better academically, the level of school dropout is reduced and the children's positive behaviour and self-esteem are enhanced (Chemagosi, Odongo & Aloka, 2016;Epstein, 1987;Kibaara & Ndirangu, 2014).…”
Section: Introductionmentioning
confidence: 99%